Legal Regulation of Misleading Commercial Advertising (A Study of Palestinian Legislation) - Adas, Noor; Khale, Ghassan; Ghanaam, Ola (Journal of Legal Sciences, 2025)
In the current landscape of advancing technology, commercial advertising is an indivisible part of the contemporary economic environment, due to the crucial role it plays in introducing consumers to various products and services through both traditional and digital channels. This advertising conveys messages that include data and essential information that enhances consumers' understanding of market trends and conditions, as well as the various types and characteristics of products and services. This knowledge helps consumers make informed decisions when selecting goods that meet their needs.However, commercial advertising can also be misused by some producers and distributors, through the use of attractive but exaggerated methods that emphasize the benefits of their products beyond legally permitted limits. and ultimately, this leads to misleading and confusing consumers about which products and services to choose. Such misleading advertising can result in decisions based on incomplete or false information. Therefore, the potential harms of misleading commercial advertising appear on the consumer, so we must highlight the need for effective legal protections against such deceptive and false advertising practices, Specifically, criminal protection.Therefore, this study is concerned with examining the relevant Legal rules and assessing the extent of the Palestinian legislator's focus on regulating commercial advertising to protect consumers from deception and negative influences. Additionally, the study focuses on the criminal protections the legislator has established to safeguard consumers against misleading commercial advertising.